Islamic religiosity, self-concept, and quarter-life crisis among undergraduate health sciences students - Fajriyah Nur Afriyanti; Eneng Erna Purnama; Tati Suryati; Rian Agus Setiawan; Achirman Achirman (Malahayati International Journal of Nursing and Health Science, 2026)
Background: The quarter-life crisis (QLC), typically occurring during emerging adulthood, represents a prolonged emotional struggle that may lead to adverse outcomes such as stress, anxiety disorders, and depression. Purpose: To examine the correlation between Islamic religiosity and self-concept with QLC among undergraduate students. Method: A quantitative correlational design with a cross-sectional approach was employed, involving 82 students. Data were collected using structured questionnaires and analyzed through univariate and bivariate techniques, with Spearman’s rank correlation applied. Results: The majority of respondents were 21 years old (52.43%), female (82.93%), and enrolled in public schools (79.27%). Most demonstrated moderate Islamic religiosity (70.73%), particularly in spiritual experiences (mean = 37.41). All students reported a positive overall self-concept, with role performance (97.56%) being the strongest dimension. Statistical analysis revealed no significant relationship between Islamic religiosity and QLC (p = 0.152, r = –0.160). However, a significant negative correlation was found between self-concept and QLC (p = 0.001, r = –0.440). While religiosity components such as spiritual experiences, consequences, and worship practices were moderately expressed, they did not significantly influence QLC. In contrast, negative aspects of self-concept—including body image, ideal self, self-esteem, role performance, and personal identity—were significantly associated with QLC. Conclusion: Self-concept was moderately and inversely associated with quarter-life crisis, whereas Islamic religiosity was not significantly associated with quarter-life crisis. The cross-sectional design does not establish causality.